Pengaruh Korean Wave dan Brand Ambassador Terhadap Keputusan Pembelian Kosmetik Korea Nature Republic (Studi Kasus Pada Konsumen Penggemar NCT 127 di Bekasi) - Novalia Elitasari Novalia Elitasari; Hanuna Shafariah Hanuna Shafariah (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study was conducted to analyze the effect of Korean Wave and Brand Ambassador on purchase decision of Korean Nature Republic cosmetics (Case Study on Consumers of NCT127 Fans in Bekasi). This study used data and information collection method by giving questionnaires to consumers of Nature Republic who were fans of NCT 127 in Bekasi with a sample of 100 people. The sampling technique used was accidental sampling. Each respondent answered 20 questions using a Likert scale. The research method used was descriptive quantitative where in this study there were 3 variables in the forms of independent variables, i.e., Korean Wave (X1), Brand Ambassador (X2) and dependent variable, i.e., Purchase Decision (Y). The results of the study indicated that the Korean Wave had a significant effect on Purchase Decision and Brand Ambassadors also had a significant effect on Purchase Decision. Korean Wave and Brand Ambassador together had a significant effect on Purchase Decision by 53%, the remaining 47% was affected by other factors not examined in this study.